The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.28945/254
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation of the IT Fundamentals Knowledge Area in an Introductory IT Course

Abstract: Executive SummaryThe recently promulgated IT model curriculum contains IT fundamentals (ITF) as one of its knowledge areas. It is intended to give students a broad understanding of (1) the IT profession and the skills that students must develop to become successful IT professionals and (2) the academic discipline of IT and its relationship to other disciplines. The model curriculum recommends 33 lecture hours to complete the IT fundamentals knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…However, there will be increased demand for expertise related to: process design, redesign, and reengineering; information design and knowledge management; change management; and the analysis of organizational readiness. Skills related to project management and a systematic understanding of the interdependence between ICT applications and organizational processes are crucial (Bullen, 2007;McAdams, 2007;Australian Government, 2006;Aasheim et al, 2006;Ekstrom et al, 2006;Gomes and Joglekar, 2005;Hildebrand, 2005;Morello, 2005;Westervelt, 2005). ICT professionals need to understand the organization's vision, mission, strategic plan, goals, culture, structure, management procedures, and social factors (Australian Government, 2006;Bell and Caldwell, 2005;Gaudin, 2005;Meredith, 2005;Morello, 2005;Plummer et al, 2005).…”
Section: Related Literature and Theoretical Framework 21mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there will be increased demand for expertise related to: process design, redesign, and reengineering; information design and knowledge management; change management; and the analysis of organizational readiness. Skills related to project management and a systematic understanding of the interdependence between ICT applications and organizational processes are crucial (Bullen, 2007;McAdams, 2007;Australian Government, 2006;Aasheim et al, 2006;Ekstrom et al, 2006;Gomes and Joglekar, 2005;Hildebrand, 2005;Morello, 2005;Westervelt, 2005). ICT professionals need to understand the organization's vision, mission, strategic plan, goals, culture, structure, management procedures, and social factors (Australian Government, 2006;Bell and Caldwell, 2005;Gaudin, 2005;Meredith, 2005;Morello, 2005;Plummer et al, 2005).…”
Section: Related Literature and Theoretical Framework 21mentioning
confidence: 99%
“…Recent studies have focused on requirements for ICT curricular designed to provide initial knowledge, skills, and experience. Aasheim et al (2006) identified five areas of knowledge which are pervasive themes and need to be included as part of ICT curricular: organizational issues; the history of ICT; related and informing disciplines; application domains; and the application of mathematics and statistics to ICT. In the United States extensive reviews of national skill standards conducted by the National Workforce Center for Emerging Technologies and the Ohio IT Competency Profile identified a wide variety of skills required in order to meet the needs of local, regional, and national markets (Floyd, 2004).…”
Section: Related Literature and Theoretical Framework 21mentioning
confidence: 99%
See 1 more Smart Citation
“…Take, for instance, a first-year "101" IT Fundamentals course taught in the U.S., as described by Aasheim, Lee, and Reichgelt (2006). The same 101 introductory course takes somewhat different form in Tumaini's BSC-IT program.…”
Section: Syllabusmentioning
confidence: 99%
“…It should involve both computer and information literacy, which means using the computer as a collection of applications, the way of communication, and the source of information (Hoffman & Blake, 2003). However, a model curriculum which formulates basic content to be included in the introductory IT courses is often hard to achieve due to the time limitations (Aasheim, Lee, & Reichgelt, 2006).…”
Section: Designing An Introductory It Coursementioning
confidence: 99%